1986
DOI: 10.1080/09553008614551211
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low-level Radiofrequency and Microwave Radiation on Brain Tissue and Animal Behaviour

Abstract: There has been much public interest and controversy about the effects of exposure to low levels of microwave and radiofrequency radiation. Of particular interest are reports of radiation-induced changes in brain tissue and animal behaviour. This review considers the evidence supporting some of these effects. The main conclusions of the review are: The levels of tracer substances in the brain tissue of conscious or anaesthetized animals can be altered by acute exposure to microwave radiation that is sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Since the windows often are very narrow, the experimental search for unique combinations of different exposure parameters among the innumerable possibilities is problematic, and it is no wonder that many attempts to reveal the effectiveness windows by probing various combinations of exposure parameters resulted in negative ®ndings [Chou and Guy, 1978;Bush et al, 1981;Liu et al, 1982;Pakhomov et al, 1992Pakhomov et al, , 1995. More information and discussion of window phenomena can be found in specialized reviews on pulsed microwave bioeffects [Blackwell and Saunders, 1986;Postow and Swicord, 1986;Pakhomov and Murphy, 2000].…”
Section: Introductionmentioning
confidence: 98%
“…Since the windows often are very narrow, the experimental search for unique combinations of different exposure parameters among the innumerable possibilities is problematic, and it is no wonder that many attempts to reveal the effectiveness windows by probing various combinations of exposure parameters resulted in negative ®ndings [Chou and Guy, 1978;Bush et al, 1981;Liu et al, 1982;Pakhomov et al, 1992Pakhomov et al, , 1995. More information and discussion of window phenomena can be found in specialized reviews on pulsed microwave bioeffects [Blackwell and Saunders, 1986;Postow and Swicord, 1986;Pakhomov and Murphy, 2000].…”
Section: Introductionmentioning
confidence: 98%
“…A number of published studies have reported enhanced effects of RF fields subjected to modulation in the extremely low frequency (ELF) range on the efflux of radioactively labelled calcium ions from brain tissue (for reviews, see Myers & Ross 1981, Liddle & Blackman 1984, Blackwell & Saunders 1986, Advisory Group on Non-ionizing Radiation 2001). In particular, a modulation frequency-dependent ''window'' (i.e., a narrow range of modulation frequencies over which an effect is observed) has been suggested with a peak around 16 Hz (Bawin & Adey 1976, Blackman et al 1979.…”
Section: Introductionmentioning
confidence: 98%
“…Microwave irradiation without hyperthermia did not open the BBB. For a review on the effects of low-level radiofrequency and microwave irradiation on brain tissue refer to Blackwell and Saunders (1986). The data of Sminia et d. (1992) show that an injurious heat dose was required to increase the uptake of cisplatin in the spinal cord.…”
Section: Effects Of Combination Of Hyperthermia Und Chemotherapy On Tmentioning
confidence: 97%